2013
DOI: 10.1111/gbi.12032
|View full text |Cite
|
Sign up to set email alerts
|

Temperature response of denitrification rate and greenhouse gas production in agricultural river marginal wetland soils

Abstract: Soils are predicted to exhibit significant feedback to global warming via the temperature response of greenhouse gas (GHG) production. However, the temperature response of hydromorphic wetland soils is complicated by confounding factors such as oxygen (O2 ), nitrate (NO3-) and soil carbon (C). We examined the effect of a temperature gradient (2-25 °C) on denitrification rates and net nitrous oxide (N2 O), methane (CH4 ) production and heterotrophic respiration in mineral (Eutric cambisol and Fluvisol) and orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 101 publications
(143 reference statements)
0
16
0
Order By: Relevance
“…Warming may increase N 2 O emissions in agricultural riparian zones and wetlands (Maag et al ., ; Munoz‐Leoz et al ., ; Soosaar et al ., ). In the United Kingdom (UK), the effects of temperature on N 2 O emissions have been studied in flooded and nonflooded agricultural floodplain wetlands, and this work has shown that flooding and warming can synergistically increase N 2 O emissions (Bonnett et al ., ). Increased flooding frequency led to higher emissions of N 2 O in an agricultural riparian zone in Indiana (Jacinthe et al ., ).…”
Section: Land Use and Climate Variability Amplify Watershed Greenhousmentioning
confidence: 97%
See 3 more Smart Citations
“…Warming may increase N 2 O emissions in agricultural riparian zones and wetlands (Maag et al ., ; Munoz‐Leoz et al ., ; Soosaar et al ., ). In the United Kingdom (UK), the effects of temperature on N 2 O emissions have been studied in flooded and nonflooded agricultural floodplain wetlands, and this work has shown that flooding and warming can synergistically increase N 2 O emissions (Bonnett et al ., ). Increased flooding frequency led to higher emissions of N 2 O in an agricultural riparian zone in Indiana (Jacinthe et al ., ).…”
Section: Land Use and Climate Variability Amplify Watershed Greenhousmentioning
confidence: 97%
“…() studied continually inundated agricultural wetlands in Ohio and found that experimentally pulsed flood flows significantly decreased CH 4 emissions. There may be other abiotic and biotic factors that are drivers of CH 4 emissions (Sovik et al ., ; Mander et al ., ; Samaritani et al ., ; Sha et al ., ) including inhibition by nitrate and N 2 O during floods (Bonnett et al ., ). Thus, the response of CH 4 to flooding and temperature can also be ecosystem specific (Le Mer and Roger, ).…”
Section: Land Use and Climate Variability Amplify Watershed Greenhousmentioning
confidence: 97%
See 2 more Smart Citations
“…Recent studies indicate that within freshwater sediments and phototrophic biofilms, warming can strongly increase denitrification rates (Bonnett et al 2013), due to temperature-regulated oxygen concentrations Bouletreau et al 2012). However, in these studies oxygen concentrations were measured in the water column, whereas most denitrification takes place in the sediment.…”
Section: Introductionmentioning
confidence: 99%